2014
DOI: 10.1515/cclm-2014-0219
|View full text |Cite
|
Sign up to set email alerts
|

May thrombopoietin be a useful marker of sepsis severity assessment in patients with SIRS entering the emergency department?

Abstract: Our preliminary results suggest that TPO may have the potential to be considered a promising early biomarker for both the diagnosis of sepsis and the assessment of sepsis severity in patients with SIRS entering the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…21 In strong contrast, we directly demonstrate that supra-steady-state enhanced Mpl stimulation drives dormant HSCs into division and expansion, a situation that might occur, for example, in sepsis-mediated inflammation. 22,23 Indeed, prior studies demonstrated that Tpo and Mpl signaling is essential for HSC homeostasis 24,25 and their expansion after transplantation, 25 whereas, seemingly contradictorily, other studies demonstrated that Tpo and Mpl signaling is critical for keeping HSCs in a quiescent state. 12,24 We suggest that this discrepancy might result from Mpl signaling strength: although data on HSC quiescence stem from loss-of-function studies, 12,24 we examined here the effect of supra-steady-state Mpl signaling, more comparable to studies on higher doses of thrombopoietin administration 12 or on genetic deficiency of lymphocyte adaptor protein, a negative regulator of Tpo-induced signaling.…”
Section: Resultsmentioning
confidence: 99%
“…21 In strong contrast, we directly demonstrate that supra-steady-state enhanced Mpl stimulation drives dormant HSCs into division and expansion, a situation that might occur, for example, in sepsis-mediated inflammation. 22,23 Indeed, prior studies demonstrated that Tpo and Mpl signaling is essential for HSC homeostasis 24,25 and their expansion after transplantation, 25 whereas, seemingly contradictorily, other studies demonstrated that Tpo and Mpl signaling is critical for keeping HSCs in a quiescent state. 12,24 We suggest that this discrepancy might result from Mpl signaling strength: although data on HSC quiescence stem from loss-of-function studies, 12,24 we examined here the effect of supra-steady-state Mpl signaling, more comparable to studies on higher doses of thrombopoietin administration 12 or on genetic deficiency of lymphocyte adaptor protein, a negative regulator of Tpo-induced signaling.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in reduced thrombus formation without change in bleeding time, or hemostatic function, and suggests a potentially safer target for pharmacotherapy for stroke and heart attack [34]. A recent study highlights the potential for TPO to be used as a biomarker in the diagnosis and assessment of sepsis severity, in patients presenting to the emergency department with systemic inflammatory response syndrome [35]. A complete evaluation of the cardiovascular effects of TPO in vivo may provide an additional clue for the development of new therapeutic interventions in the setting of cardiovascular disease [16].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of TPO are increased in inflammatory states as a result of IL-6 stimulation [14]. In the ED the plasma TPO concentration was significantly higher in patients with SIRS secondary to infection compared to those with non-septic SIRS [15]. In the ED the plasma TPO concentration was significantly higher in patients with SIRS secondary to infection compared to those with non-septic SIRS [15].…”
Section: Thrombopoietin (Tpo)mentioning
confidence: 99%